Evaluation of Formation Damage from Transient Pressure Analysis: Unsteady State Skin Factor - El-Khatib, Noaman A.F. (2011)
The damaged zone around the well is considered as the internal region of a composite system comprising two regions of different permeabilities. An analytical solution is obtained in Laplace space and is inverted using Stehfest Algorithm. The actual skin factor is obtained as the difference in dimensionless pressure at the well of the composite system and that of the homogeneous system at the same dimensionless time. The ratio of the actual skin factor to the steady state skin factor is estimated and correlated with the permeability ratio and the dimensionless depth of invasion. The additional pressure drop due to damage is found to be time dependent and varies from zero at the start and approaches the steady state skin factor at very large dimensionless time. The unsteady state skin factor and skin factor ratio depends on both the permeability ratio and the dimensionless radius of invasion and not uniquely on their combination. The developed model and the correlation charts can be used to evaluate the formation damage from well test analysis around the well by estimating both the skin permability and the depth of invasion in the damaged zone. This is an improvement over the conventional welltesting methods that give the steady state skin factor which is a combination of both permeability ratio and the depth of invasion.